2016
DOI: 10.1111/hdi.12450
|View full text |Cite
|
Sign up to set email alerts
|

Extranasal Staphylococcus aureus colonization predisposes to bloodstream infections in patients on hemodialysis with noncuffed internal jugular vein catheters

Abstract: Extranasal S. aureus carriage is as significant a risk factor as nasal carriage for staphylococcal infections in patients on HD through catheters. The study is limited by lack of molecular phenotyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Staphylococcus was also found to occur in RO water by Gomila et al [38]. Moreover, it was revealed that Staphylococcus aureus could increase the risk of invasive infection of hemodialysis patients [39,40]. The high level of these genera alerts the existence of certain occult microbial contaminations in RO effluent that could generate enormous risk to dialysis patients, and prompts the remedy of the insufficient traditional method that ignores the detection of uncultured or VBNC bacteria [38].…”
Section: Structure and Diversity Analyses Of Microbial Communitymentioning
confidence: 99%
“…Staphylococcus was also found to occur in RO water by Gomila et al [38]. Moreover, it was revealed that Staphylococcus aureus could increase the risk of invasive infection of hemodialysis patients [39,40]. The high level of these genera alerts the existence of certain occult microbial contaminations in RO effluent that could generate enormous risk to dialysis patients, and prompts the remedy of the insufficient traditional method that ignores the detection of uncultured or VBNC bacteria [38].…”
Section: Structure and Diversity Analyses Of Microbial Communitymentioning
confidence: 99%
“…Also, in another study carried out by Devraj et al S. aureus colonization in throat were observed in 11.4% of hemodialysis patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…17 The risk of infections in nasal carriers of this microorganism is real and well defined. 18 It is important to point out that the small number…”
Section: Discussionmentioning
confidence: 99%